1992
DOI: 10.1071/wf9920021
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of Savanna Fires in Senegal and the Gambia, West Africa, 1989-90, Derived From Multi-Temporal AVHRR Night Images

Abstract: Quantitative data on fire regimes from the world's savannas have previously been difficult to obtain due to logistical and scientific reasons. This study addresses the issue for Senegal and The Gambia, West Africa. A bispectral satellite image based method for fire detection has recently been improved and made semi-automatic to provide information on fire regimes of savannas. The method uses thermal night time data from the Advanced Very High Resolution Radiometer (AVHRR) onboard the National Oceanic and Atrno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 9 publications
2
22
0
1
Order By: Relevance
“…Satellite observations have shown that forest fires exhibit strong diurnal cycles (Giglio, 2007;Prins et al, 1998;Langaas, 1992;Cahoon et al, 1992;Menzel and Prins, 1996;Eva and Lambin, 1998;Pack et al, 2000). Peak burning typically occurs from 13:00 to 18:30 local time and distinctly earlier in heavily forested regions in the tropics and subtropics (Giglio, 2007).…”
Section: Temporal Constraints On Biomass Burning Emissionsmentioning
confidence: 99%
“…Satellite observations have shown that forest fires exhibit strong diurnal cycles (Giglio, 2007;Prins et al, 1998;Langaas, 1992;Cahoon et al, 1992;Menzel and Prins, 1996;Eva and Lambin, 1998;Pack et al, 2000). Peak burning typically occurs from 13:00 to 18:30 local time and distinctly earlier in heavily forested regions in the tropics and subtropics (Giglio, 2007).…”
Section: Temporal Constraints On Biomass Burning Emissionsmentioning
confidence: 99%
“…For the West Africa region, one could mention the work done by Langaas [21], more particularly on the diurnal fire cycle, or by Kennedy et al [22] and Grégoire [23] on the seasonal distribution. In the specific case of the protected areas of the SUN network, Eva et al [24] and Grégoire and Simonetti [25,26] have done a systematic monitoring of fire activity in these protected areas since 2004.…”
Section: Open Accessmentioning
confidence: 99%
“…Savanna fires are typically lit earlier in the day [2], and as the day progresses, hotter and drier conditions in the afternoon promote faster fire spread rates, longer active fire perimeters, and increased fireline intensities [3]. After the mid-day peak in optimum burning conditions, air temperature decreases, relative humidity increases, and fire behaviour subsides.…”
Section: Introductionmentioning
confidence: 99%
“…After the mid-day peak in optimum burning conditions, air temperature decreases, relative humidity increases, and fire behaviour subsides. Whilst smaller agricultural and pastoral fires tend to extinguish during the evening [4], many uncontrolled fires burning across Africa's uninterrupted landscapes persist well into the night [2].…”
Section: Introductionmentioning
confidence: 99%